Two Targets, Two Instruments : Monetary and Exchange Rate Policies in Emerging Market Economies - Ghosh, Atish (Staff Discussion Notes; Staff Discussion Notes ;, 2012)
Staff Discussion Notes showcase the latest policy-related analysis and research being developed by individual IMF staff and are published to elicit comment and to further debate. These papers are generally brief and written in nontechnical language, and so are aimed at a broad audience interested in economic policy issues. This Web-only series replaced Staff Position Notes in January 2011.